Cold polypectomy for duodenal adenomas: a prospective clinical trial - Maruoka, Daisuke; Matsumura, Tomoaki; Kasamatsu, Shingo; Ishigami, Hideaki; Taida, Takashi; Okimoto, Kenichiro; Nakagawa, Tomoo; Katsuno, Tatsuro; Arai, Makoto (Endoscopy, 2017)
Background and study aims Endoscopic resection is effective in treating nonampullary duodenal adenomas but has a high incidence of complications. Cold polypectomy, including cold forceps polypectomy (CFP) and cold snare polypectomy (CSP), is safe and effective in treating colorectal polyps. However, its utility in sporadic nonampullary duodenal adenomas has not been investigated. The purpose of this prospective study was to examine the safety and efficacy of cold polypectomy for sporadic nonampullary duodenal adenomas.Patients and methods Between March 2015 and June 2016, patients who were endoscopically diagnosed with sporadic nonampullary duodenal adenomas up to 6 mm underwent cold polypectomy. Patients with pathologically confirmed adenomas underwent endoscopic biopsy 3 months after resection. The main outcomes of interest were incomplete resection and complications.Results Overall, 39 lesions in 30 patients were removed via cold polypectomy (CFP, 9 lesions in 8 patients; CSP, 30 lesions in 22 patients). Seven of 9 (77.8 %) and 29 of 30 (96.7 %) lesions were removed en bloc via CFP and CSP, respectively. Pathologically, 34 of the 39 lesions (87.2 %) were confirmed as adenomas, and their mean size was 3.9 ± 1.2 mm (range 2 – 6 mm). Of the 34 adenomas, 20 (58.8 %) were R0 resection lesions, of which 3 of 9 (33.3 %) and 17 of 25 (68.0 %) had undergone CFP and CSP, respectively. No delayed bleeding or intraprocedural/delayed perforation was observed. All 30 patients with the 34 pathologically confirmed adenomas underwent upper gastrointestinal endoscopy 3 months after cold polypectomy, and no morphological or pathological recurrence was identified.Conclusions In this small study, cold polypectomy appeared to be safe and effective in treating diminutive and small sporadic nonampullary duodenal adenomas.(Clinical trial registration number: UMIN000016829)